VD_FINDINFO HC / 2015 / 136 vom 23. Januar 2015 - VD Tribunal cantonal (2015)
ASSISTANCE JUDICIAIRE, INDEMNITÉ ÉQUITABLE, AVOCAT D'OFFICE | 119 al. 1 CPC (CH), 119 al. 4 CPC (CH), 122 al. 1 let. a CPC (CH), 2 al. 1 RAJ